Family Load Caregiver (Studies in Families of People with Mental Disorders in the Work Area of the Kebasen Health Center, Banyumas Regency in 2020) - Dyah Wahyuningsih; Widyo Subagyo; Mukhadiono Mukhadiono (Budapest International Research and Critics University, 2022)
People with mental disorders generally experience disability in various ways, so they really need their families as caregivers. Those conditionscreates a burden for his family, both subjective and objective burdens. The purpose of the study was to describe the burden on the family as a caregiver who takes care of family members with mental disorders in the working area of the Kebasen Health Center.This type of research is descriptive analytic research. The number of samples as many as 45 families who have family members with mental disorders and taken by purposive sampling technique. Collecting data using a questionnaire. Data analysis was carried out by univariate analysis in the form of a frequency distribution.The results of the study prove that sall respondents experience the burden of caring for family members who have mental disorders. The highest burden was at the moderate level, as many as 29 people (64.44%). Next are heavy loads as many as 10 people (22.22%) and lastly light loads as many as 6 people (13.33%). The difference in caregiver burden lies in the level of perceived burden.